Caveolin‐3 deficiency associated with the dystrophy P104L mutation impairs skeletal muscle mitochondrial form and function. Issue 3 (23rd February 2020) - Shah, Dinesh S.; Nisr, Raid B.; Stretton, Clare; Krasteva‐Christ, Gabriela; Hundal, Harinder S.
Abstract: Background: Caveolin‐3 (Cav3) is the principal structural component of caveolae in skeletal muscle. Dominant pathogenic mutations in the Cav3 gene, such as the Limb Girdle Muscular Dystrophy‐1C (LGMD1C) P104L mutation, result in substantial loss of Cav3 and myopathic changes characterized by muscle weakness and wasting. We hypothesize such myopathy may also be associated with disturbances in mitochondrial biology. Herein, we report studies assessing the effects of Cav3 deficiency on mitochondrial form and function in skeletal muscle cells. Methods: L6 myoblasts were stably transfected with Cav3 P104L or expression of native Cav3 repressed by shRNA or CRISPR/Cas9 genome editing prior to performing fixed/live cell imaging of mitochondrial morphology, subcellular fractionation and immunoblotting, or analysis of real time mitochondrial respiration. Skeletal muscle from wild‐type and Cav3 −/− mice was processed for analysis of mitochondrial proteins by immunoblotting. Results: Caveolin‐3 was detected in mitochondrial‐enriched membranes isolated from mouse gastrocnemius muscle and L6 myoblasts. Expression of Cav3 P104L in L6 myoblasts led to its targeting to the Golgi and loss of native Cav3 (>95%), including that associated with mitochondrial membranes. Cav3 P104L reduced mitochondrial mass and induced fragmentation of the mitochondrial network that was associated with significant loss of proteins involved in mitochondrial biogenesis, respiration, morphology, and redox function [i.e. PGC1α, succinate dehyrdogenase (SDHA), ANT1, MFN2, OPA1, and MnSOD). Furthermore, Cav3 P104L myoblasts exhibited increased mitochondrial cholesterol and loss of cardiolipin. Consistent with these changes, Cav3 P104L expression reduced mitochondrial respiratory capacity and increased myocellular superoxide production. These morphological, biochemical, and functional mitochondrial changes were phenocopied in myoblasts in which Cav3 had been silenced/knocked‐out using shRNA or CRISPR. Reduced mitochondrial mass, PGC1α, SDHA, ANT1, and MnSOD were also demonstrable in Cav3 −/− mouse gastrocnemius. Strikingly, Cav3 re‐expression in Cav3KO myoblasts restored its mitochondrial association and facilitated reformation of a tubular mitochondrial network. Significantly, re‐expression also mitigated changes in mitochondrial superoxide, cholesterol, and cardiolipin content and recovered cellular respiratory capacity. Conclusions: Our results identify Cav3 as an important regulator of mitochondrial homeostasis and reveal that Cav3 deficiency in muscle cells associated with the Cav3 P104L mutation invokes major disturbances in mitochondrial respiration and energy status that may contribute to the pathology of LGMD1C.